2010
DOI: 10.1375/prp.4.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Review of Refugee Mental Health Assessment: Best Practices and Recommendations

Abstract: T his article focuses on mental health assessment of refugees in clinical, educational and administrative-legal settings in order to synthesise research and practice designed to enhance and promote further development of culturally appropriate clinical assessment services during the refugee resettlement process. It specifically surveys research published over the last 25 years into the development, reliability measurement and validity testing of assessment instruments, which have been used with children, adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 54 publications
0
22
0
2
Order By: Relevance
“…Considering the significant differences in the assessment of children compared to adults, and the significant impact of trauma on child development, there is an urgent need for the development of validated tools for refugee children. This severe lack of screening and assessment tools is more profound for preschool-age children (Davidson, Murray, & Schweitzer, 2010; Gadeberg et al, 2017; Lieberman, Chu, Van Horn, & Harris, 2011). Early trauma can induce toxic stress in terms of the normal course of developmental processes, and early trauma screening is essential to intervene on time, before ongoing stress leads to the development of negative outcomes and further pathology.…”
Section: Reflections For Future Researchmentioning
confidence: 99%
“…Considering the significant differences in the assessment of children compared to adults, and the significant impact of trauma on child development, there is an urgent need for the development of validated tools for refugee children. This severe lack of screening and assessment tools is more profound for preschool-age children (Davidson, Murray, & Schweitzer, 2010; Gadeberg et al, 2017; Lieberman, Chu, Van Horn, & Harris, 2011). Early trauma can induce toxic stress in terms of the normal course of developmental processes, and early trauma screening is essential to intervene on time, before ongoing stress leads to the development of negative outcomes and further pathology.…”
Section: Reflections For Future Researchmentioning
confidence: 99%
“…??? Davidson, Murray, and Schweitzer (2008), found that refugees have poorer general health; poorer mental health including increased somatisation and dissociation; increased levels of psychological distress including susceptibility to posttraumatic stress disorder (PTSD), anxiety and depression; impairments in cognitive function; low perceptions of educational achievement and career aspirations; a lack of family cohesion and reduced feelings of belonging.…”
Section: Global Diasporas and The Refugee Experiencementioning
confidence: 99%
“…However, the measures have been used in several previous studies examining Russian and Kurdish origin populations . Additionally, the cut‐off point of the HSCL‐25 scale has not been validated among the populations under study, despite its good cross‐cultural reliability and validity . Nevertheless, one of the strengths of our study is that current affective symptoms were considered when assessing the associations between PTEs, PD and substance use.…”
Section: Discussionmentioning
confidence: 99%